Cultural differences regarding expected utilities and costs of plagiarism: Preliminary results of an international survey study - Eckhard Burkatzki; Wolfgang Gerstlberger; Joost Platje (Economic and Environmental Studies (E&ES), 2012)
The study presented asks for cultural variations regarding the perceived utilities and costs of plagiarism. It focuses on the following three questions: (1) Do students from countries with a different social capital of generalized trust vary with respect to the average frequency of plagiarism? (2) Do students from countries with a different capital of generalized trust vary with respect to the on average perceived cost-utility structure of plagiarizing? (3) Is it possible to explain observed country-specific differences in the aggregated frequency of plagiarism by different country-specific perceptions of the cost-utility-structure of plagiarizing? To answer these questions the findings of empirical research in Poland, Germany and Denmark are presented. Methodically the investigation is based on bivariate statistics, Principle Component Analyses and Multiple Regression. The findings show that there exist significant differences regarding both the frequency of plagiarism and the willingness to plagiarize between high-trust-, medium-trust- and low-trust-populations. Especially within high-trust-populations the perceived moral costs of plagiarizing activity is a stronger disincentive for committing plagiarism than possible external sanctions. Furthermore, a reverse effect of administrative sanctions within high-trust- and low-trust-populations could be observed, with the remarkable recognition that in high-trust-populations the threat of administrative sanctions does not prevent but provoke deviance. Regression results give evidence that differences in the aggregated frequency of plagiarism between different populations could be explained by the activity of utility-oriented actors under circumstances of a varying social and cultural structure. The level of generalized trust in a population in this connection is a critical cultural factor, since it has strong influence on how students especially perceive the moral costs of plagiarism.
Keywords: 330; plagiarism; trust; high-trust societies; low-trust societies; Denmark; Germany; Poland